Neural control of force output during maximal and submaximal exercise - St. Clair Gibson, A.; Lambert, M. L.; Noakes, T. D. (Sports Medicine, 2001)
A common belief in exercise physiology is that fatigue during exercise is caused by changes in skeletal muscle metabolism. This 'peripheral' fatigue results either from substrate depletion during submaximal exercise or metabolite accumulation during maximal exercise in the exercising muscles. However, if substrate depletion alone caused fatigue, intracellular ATP levels would decrease and lead to rigor and cellular death. Alternatively, metabolite accumulation would prevent any increase in exercise intensity near the end of exercise. At present, neither of these effects has been shown to occur, which suggests that fatigue may be controlled by changes in efferent neural command, generally described as 'central' fatigue. In this review, we examine neural efferent command mechanisms involved in fatigue, including the concepts of muscle wisdom during short term maximal activity, and muscle unit rotation and teleoanticipation during submaximal endurance activity. We propose that neural strategies exist to maintain muscle reserve, and inhibit exercise activity before any irreparable damage to muscles and organs occurs. The finding that symptoms of fatigue occur in the nonexercising state in individuals with chronic fatigue syndrome indicates that fatigue is probably not a physiological entity, but rather a sensory manifestation of these neural regulatory mechanisms.